Biblio Counseling To Reduce The Effectiveness Of Student Academic Procrastination Force Of Guidance And Counseling - Prakoso, Erik Teguh; Kristianti, Wida Reni (JURNAL KONSELING GUSJIGANG, 2018)
Academic Procrastination is a manifestation form of avoidance in a task that should be done by an individual. Procrastinator deliberately to delay the work or tasks that should be solved. This study use a quantitative approach to design Quasi Experiment patterns  pretest and posttest Group. The subjects in this study is the Student Guidance and Counseling Program 2015 University Kanjuruhan Malang forces amounting to 5 students. The research instrument uses a scale of academic procrastination. The results showed that based on the analysis of different test Wilcoxon between pretest and posttest generate value significant (two-tailed) <0.05 is 0.043, which means the provision of treatment through counseling biblio effective to reduce the level of student academic procrastination. Based on the results of data presentation can be concluded that the study subjects experienced the difference after the treatment is done, so it can be said that the biblio effective counseling to reduce the level of academic procrastination.